Jejak Sejarah Pergerakan Nasional: Sumpah Pemuda sebagai Pemersatu Bangsa - Khumaeroh, Siti; Alchumairoh, Siti Aisyah; Ajmain, Maftuh (AHKAM, 2025)
This research aims to commemorate Indonesia's struggle for independence which is centered on the historic event of the Youth Pledge. In the Second Youth Congress held on October 28, 1928, three main principles were established for unity: one bloodshed, one nation, and one language—Indonesia. This event marked the awareness of Indonesian youth of the importance of working together to fight colonialism. History of the Youth Pledge: Various youth organizations, especially regional ones, such as Jong Java, Jong Sumatranen Bond, and Jong Bataks Bond, emerged initially. The Youth Pledge has had a significant influence in the history of the national struggle. Apart from fostering a sense of nationalism, this event instills the principles of unity, mutual cooperation and social responsibility in society. The spirit of the Youth Pledge became the basis of the struggle for Indonesian independence on August 17 1945. Apart from that, the Youth Pledge forms the identity of the Indonesian nation which respects diversity and Bhinneka Tunggal Ika.